(3cfR GdeYGfj aj TQM MQR GdCeGfjs - (3eMeO Hf CMeO Hf eMeO Hf GdMSjf GdehUdj GdebQj GdMfHdj GdeYQha HTYdgs; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3hHYO adeG JQJHJ eRjI GdYdhe Ydi eRjI YQGjSgG dfaGFS hHOGjYgG GdQhGFY s
(3BNQgG (B:s
(3hgPG BNQ eG ChQOfGg ef EjVGM cfR GdeYGfj aj MQR GdCeGfj s
(3GdfSNI HgG MhGTs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdbQGAGJ hGdJLhjOs